Coordination of the Eurasian Economic Union member states diplomacy in the United Nations - Leshenyuk, Oleg N. (Journal of the Belarusian State University. International Relations, 2021)
This article offers recommendations for optimising the coordination of diplomacy of the Eurasian Economic Union member states within the United Nations system. Significant changes in the modern diplomatic activities of the Ministry of Foreign Affairs of the Republic of Belarus have occurred which caused changes in the forms of diplomatic interaction. Currently, diplomatic interactions acquire a network character. The article also provides examples of new opportunities for negotiations and initiatives considering the networked nature of international relations and shows the forms of network interaction of the Ministry of Foreign Affairs of the Republic of Belarus, as well as current examples of network diplomacy. The necessity to complicate the forms of coordination and introduce them into international organisations into the United Nations system is pointed out. Recommendations are given to the EEU member states, as well as to Eurasian integration associations. An analysis of the work shows that for the effective activities of the subjects of international relations it is necessary to integrate into complex network interactions. This can be implemented basing on the existing structure of the Union State, the EEU, the CIS, the CSTO, as well as Eurasian non-profit and commercial organisations.
Keywords: Republic of Belarus; the UN system; foreign policy; diplomacy; Eurasian Economic Union; international networks; networking; network interactions; international relations; negotiations; ministry of foreign affairs